2017
DOI: 10.1021/acscatal.7b00840
|View full text |Cite
|
Sign up to set email alerts
|

Merger of Visible-Light Photoredox Catalysis and C–H Activation for the Room-Temperature C-2 Acylation of Indoles in Batch and Flow

Abstract: A mild and versatile protocol for the C–H acylation of indoles via dual photoredox/transition-metal catalysis was established in batch and flow. The C–H bond functionalization occurred selectively at the C-2 position of N-pyrimidylindoles. This room-temperature protocol tolerated a wide range of functional groups and allowed for the synthesis of a diverse set of acylated indoles. Various aromatic as well as aliphatic aldehydes (both primary and secondary) reacted successfully. Interestingly, significant accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(54 citation statements)
references
References 84 publications
1
51
0
2
Order By: Relevance
“…The photoredox activation of monochloroacetic acid leads to the formation of precipitate during the reaction (see Figure 4), again indicating catalyst precipitation/ deactivation. Works in the group of Noël and others have revealed that flow chemistry can increase the rate and yield of photoredox reactions significantly [47][48][49][50][51][52][53]. According to the law of Lambert-Beer, only the outer shell of a batch reactor (vial or Schlenk flask) is excited efficiently.…”
Section: Resultsmentioning
confidence: 99%
“…The photoredox activation of monochloroacetic acid leads to the formation of precipitate during the reaction (see Figure 4), again indicating catalyst precipitation/ deactivation. Works in the group of Noël and others have revealed that flow chemistry can increase the rate and yield of photoredox reactions significantly [47][48][49][50][51][52][53]. According to the law of Lambert-Beer, only the outer shell of a batch reactor (vial or Schlenk flask) is excited efficiently.…”
Section: Resultsmentioning
confidence: 99%
“…In this field, Eycken et al published a novel and selective C-2 acylation protocol for N-pyrimidylindoles involving C-H activation (Scheme 11). 16 One of the major drawbacks of batch photochemical reactions is the light attenuation effect through absorbing media (Bouguer-Lambert-Beer law). Thus, scaling the reaction by increasing the reactor dimensions becomes particularly difficult.…”
Section: Syn Thesismentioning
confidence: 99%
“…The growing interest in visible-light-mediated photoredox catalysis stems from its ability to promote bond formation under mild reaction conditions.D espite considerable advances in the field of HAT-mediated photocatalytic activation of different C sp 3 ÀHbonds, [1,2] the corresponding methods for the selective activation of C sp 2 (O)ÀHb onds have remained comparatively underdeveloped. [3] Aldehydes are cheap and commercially available,w hich makes them abundant surrogates for the facile generation of acyl radicals.T he strategies reported to date utilize either superstoichiometric amounts of strong oxidant [4] or harsh reaction conditions,s uch as high temperatures [5] or UV-light irradiation, [6] in order to generate an acyl radical by direct homolysis of the C(O) À Hb ond, thereby limiting such processes mainly to aromatic aldehydes (Scheme 1a). These major drawbacks have prompted the development of ac atalytic system that would enable the generation of acyl radicals under milder reaction conditions, hence providing aversatile platform that can also be extended to the branched aliphatic aldehydes and other XC(O)ÀH (X = N, O) bonds,w hich are known to undergo facile decarbonylation under harsh reaction conditions.…”
mentioning
confidence: 99%